Effect of presumptive co-trimoxazole prophylaxis on pneumococcal colonization rates, seroepidemiology and antibiotic resistance in Zambian infants: a longitudinal cohort study - CJ Gill; V Mwanakasale; MP Fox; R Chilengi; M Tembo; M Nsofwa; V Chalwe; L Mwananyanda; D Mukwamataba; B Malilwe; D Champo; WB Macleod; et al. (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To ascertain the microbiological consequences of WHO's recommendation for presumptive co-trimoxazole prophylaxis for infants with perinatal HIV exposure. METHODS: Using a longitudinal cohort design, we followed HIV-exposed and HIV-unexposed infants trimonthly for up to 18 months per infant. HIV-exposed infants received daily co-trimoxazole prophylaxis from 6 weeks to > 12 months of age. Using Streptococcus pneumoniae as our sentinel pathogen, we measured how co-trimoxazole altered nasopharyngeal colonization, pneumococcal resistance to antibiotics and serotype distribution as a function of co-trimoxazole exposure. FINDINGS: From 260 infants followed for 3096 patient-months, we detected pneumococci in 360/1394 (25.8%) samples. HIV-exposed infants were colonized more frequently than HIV-unexposed infants (risk ratio, RR: 1.4; 95% confidence interval, CI: 1.0-1.9, P = 0.04). Co-trimoxazole prophylaxis reduced colonization by ca 7% but increased the risk of colonization with co-trimoxazole-resistant pneumococci within 6 weeks of starting prophylaxis (RR: 3.2; 95% CI: 1.3-7.8, P = 0.04). Prophylaxis with co-trimoxazole led to a small but statistically significant increase of nasopharyngeal colonization with pneumococci not susceptible to clindamycin (RR: 1.6; 95% CI: 1.0-2.6, P = 0.04) but did not increase the risk of non-susceptibility to penicillin (RR: 1.1; 95% CI: 0.7-1.7), erythromycin (RR: 1.0; 95% CI: 0.6-1.7), tetracycline (RR: 0.9; 95% CI: 0.6-1.5) or chloramphenicol (RR: 0.8; 95% CI: 0.3-2.3). Co-trimoxazole prophylaxis did not cause the prevailing pneumococcal serotypes to differ from those that are targeted by the 7-valent conjugate pneumococcal vaccine (RR: 1.0; 95% CI: 0.7-1.6). CONCLUSION: Co-trimoxazole prophylaxis modestly suppresses pneumococcal colonization but accelerates infant acquisition of co-trimoxazole- and clindamycin-resistant pneumococci. Co-trimoxazole prophylaxis appears unlikely to compromise the future efficacy of conjugate vaccines.